Work experiences of an editor of Lorenzo Da Ponte "Memorie" (Prassi Ecdotiche della Modernità Letteraria, 2019)
The essay provides a case study concerning Lorenzo Da Ponte’s Memorie: two editions were published in New York in the second decade of the 19th century, but they did not spread widely in Europe. The reference edition in Italy is still the one published in 1918 by Giovanni Gambarin and Fausto Nicolini. Although it could be considered a serious work (expecially because it compares the two prints edited by the author), it is not properly a critical edition. However, due to the difficulties of the collation, it would be hard to improve it. Here the text of the Orazione (a long speech held in 1828 and included in the fifth part of the autobiography) is presented, with some questions about the possibility of a ‘separated’ edition and the definition of the textual rendering criteria. A ‘critically verified’ reconstruction like this could hopefully open a reflection about alternative editions, when the traditional ones are not possible due to a lack of resources or academic credit.
Keywords: Da Ponte Lorenzo; Memoirs; Prayer; autobiography; Nineteenth century; Philology; Textual criticism; Edition; Critical Edition; Laterza; Scrittori d'Italia; Giovanni Gambarin; Fausto Nicolini; New York